Iridoids Analysis by Different Analytical Techniques and its Role as Pharmacologic Agents: A Review - Verma, Rishabh; Arshad, M. F.; Grover, Parul; Kaur, Jasmeet; Gandhi, Neha; Das, Vishnu; Taleuzzaman, Mohamad (Current Bioactive Compounds, 2022)
Iridoids are monoterpenoids classed with a cyclopentanopyran framework and detected in various plants and certain special animals. In plants, it exists as glycosides, generally bound to glucose. Around six hundred iridoid glycosides are available in fifty-seven families of plants. Iridoids are abundant in dicotyledonous plants belonging to the Diervillaceae, Loganiaceae, Apocynaceae, Scrophulariaceae, Lamiaceae, and Rubiaceae families. Analytical techniques like chromatography, NMR, UPLC, etc., are used for the identification, separation, and estimation of either herbal extracts or formulations of iridoids. Advanced analytical techniques are useful for precise and accurate quantification of active ingredients responsible for therapeutic effects. They can be achieved by a developed and validated robust analytical method. Iridoids have shown diverse pharmacological properties. Some of the important activities are immunomodulatory, neuroprotective, anti-inflammatory, hepatoprotective, and cardio-protective effects. The other important activities are antimicrobial, antioxidant, hypoglycemic, hypolipidemic, anticancer, choleretic, antispasmodic, and purgative activities attributed to iridoids. There were not many efforts made in the past to gather and review the literature on various aspects of iridoids. This review article has collected a myriad of literature on old and advanced analytical techniques, including method development and validation of methods for quantitative and qualitative analysis of iridoids. The review also emphasizes the role of iridoids in the prevention of various ailments.
Keywords: Iridoids glucoside